Content and main elements of ecological and economic security of territorial communities - Hekov, Maksym (National Technical University "Kharkiv Polytechnic Institute", 2025)
This theses explores the environmental and economic security of territorial communities as a fundamental component of sustainable development and environmental protection. It emphasizes the integration of economic efficiency and ecological responsibility, identifying key components and tools for enhancing community resilience, and outlines current challenges and prospects for further development.
Keywords: environmental and economic security; sustainable development; green economy; environmental management; territorial communities; environmental protection